Inotilone and related phenylpropanoid polyketides from Inonotus sp. and their identification as potent COX and XO inhibitors - V. Kemami Wangun, Hilaire (Organic & Biomolecular Chemistry, 2016)
Arthritis is a general term for severe inflammatory processes in joints or joint tissue. Nonsteroidal anti-inflammatory drugs , such as diclofenac and indomethacin, have emerged the most commonly used anti- inflammatory agents for the therapy of rheumatoid arthritis. Many of these drugs target cyclooxygenases (COX), which catalyze the first two steps in the biosynthesis of the prostaglandins from the substrate arachidonic acid. In this context, the selective inhibition of enzyme subtypes, COX-1 and COX-2, has become an important goal. In contrast to rheumatoid arthritis, gouty arthritis is mediated by the crystallisation of uric acid (UA) in the joints. Gout can be treated with drugs that either increase the urinary excretion of UA, or with xanthine oxidase (OX) inhibitors that block the terminal step of UA biosynthesis. The purine analogue allopurinnol is currently the only XO inhibitor in clinical use. Unfortunately, it seems to be associated with an infrequently but severe hypersensitivity. Thus, the search for new potent inhibitors of these enzymes, which could be useful as lead structures for new anti- inflammatory and anti- arthritic therapeutics, plays a pivotal role. Here we report on the isolation, structural elucidation and biological evaluation of natural anti- inflammatory COX and XO inhibitors from the mushroom Inonotus sp.